PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zerra Restavia Finandra Hana; Aulia Fuad Rahman (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research aims to determine the effect CSR activities disclosure on financial performance in the telecommunication companies listed on the Indonesia Stock Exchange. This research uses the Corporate Social Disclosure Index (CSDI) as a measure for determining the CSR activity, based on the indicators of the Global Reporting Initiatives (GRI). The samples used in this study are 5 telecommunication companies listed in Indonesia Stock Exchange during the period 2007 to 2012. Data were analyzed using multiple linear regression analysis techniques. These results indicate that the CSR disclosure variable had no effect on financial performance. But these results indicate that the CSR disclosure variable had effect on stock returns.   Keywords: Corporate Social Responsibility (CSR), financial performance, stock returns, telecommunication companies.